Ministry Of Finance Decree No. 256 Of The Year 2015 Concerning Amending Certain Provisions of the Executive Regulations of the Customs Law Promulgated by Decree of the Minister of Finance no. 10 of the Year 2006 = وزراة المالية قرار رقم 256 لسنة 2015 بتعديل بعض أحكام اللائحة التنفيذية لقانون الجمارك الصادرة بقرار وزير المالية رقم 10 لسنة 2006 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic